Semitendinosus Tendon Augmentation for Prevention of Proximal Junctional Failure. Issue 4 (15th February 2021) - Alluri, Ram; Kim, Andrew; Ton, Andy; Kang, Hyunwoo; Acosta, Frank; Hah, Raymond
Abstract : Study Design: Retrospective cohort study. Objective: The aim of this study was to compare the incidence of proximal junctional kyphosis (PJK), proximal junctional failure (PJF), and clinical outcomes of patients who did and did not receive posterior ligament complex (PLC) augmentation using a semitendinosus allograft when undergoing long-segment posterior spinal fusion for adult spinal deformity. Summary of Background Data: Clinical research on the augmentation of the PLC to prevent PJK and PJF has been limited to small case series without a comparable control group. Methods: From 2014 to 2019, a consecutive series of patients with adult spinal deformity who underwent posterior long-segment spinal fusion with semitendinosus allograft to augment the PLC (allograft) or without PLC augmentation (control) were identified. Preoperative and postoperative spinopelvic parameters were measured. PJK, PJF, and Oswestry Disability Index (ODI) scores were recorded and compared between the two groups. Univariate and multivariate analysis was performed. P ⩽ 0.05 was considered significant. Results: Forty-nine patients in the allograft group and 34 patients in the control group were identified. There were no significant differences in demographic variables or operative characteristics between the allograft and control group. Preoperative and postoperative spinopelvic parameters were also similar between the two groups. PJK was present in 33% of patients in the allograft group and 32% of patients in the control group ( P  = 0.31). PJF did not occur in the allograft group, whereas six patients (18%) in the control group developed PJF ( P  = 0.01). Postoperative absolute ODI was significantly better in the allograft group ( P  = 0.007). Conclusion: The utilization of semitendinosus allograft tendon to augment the PLC at the upper instrumented vertebrae in patients undergoing long-segment posterior spinal fusion for adult deformity resulted in a significant decrease in PJF incidence and improved functional outcomes when compared to a cohort with similar risk of developing PJK and PJF Level of Evidence: 3 Abstract : In a matched cohort of patients who did and did not undergo posterior ligamentous complex using semitendinosus allograft tendon, the use of allograft augmentation resulted in a significant decrease in PJF incidence and improved functional outcomes.